Analysis of the Liquefaction Potential at the Base of the San Marcos Dam (Cayambe, Ecuador)—A Validation in the Use of the Horizontal-to-Vertical Spectral Ratio - Olegario Alonso-Pandavenes; Francisco Javier Torrijo; Gabriela Torres (Geosciences, 2024)
Ground liquefaction potential analysis is a fundamental characterization in areas with continuous seismic activity, such as Ecuador. Geotechnical liquefaction studies are usually approached from dynamic penetration tests, which pose problems both in their correct execution and in their evaluation. Our research involves analyzing dynamic penetration tests and microtremor geophysical surveys (horizontal-to-vertical spectral ratio technique, HVSR) for analyzing the liquefaction potential at the base of the San Marcos dam, a reservoir located in Cayambe canton (Ecuador). Based on the investigations performed at the time of construction of the dam (drilling and geophysical refraction profiles) and the application of 20 microtremor observation stations via the HVSR technique, an analysis of the safety factor of liquefaction (SFliq) was conducted using the 2001 Youd and Idriss formulation and the values of the standard penetration test (SPT) applied in granular materials (sands). In addition, the vulnerability index (Kg) proposed by Nakamura in 1989 was analyzed through the HVSR records related to the ground shear strain (GSS). The results obtained in the HVSR analysis indicate the presence of a zone of about 100 m length in the central part of the foot of the dam, whose GSS values identified a condition of susceptibility to liquefaction. In the same area, the SPT essays analysis in the P-8A drill hole also shows a potential susceptibility to liquefaction in earthquake conditions greater than a moment magnitude (Mw) of 4.5. That seismic event could occur in the area, for example, with a new activity condition of the nearby Cayambe volcano or even from an earthquake from the vicinity of the fractured zone.